KEPEMIMPINAN TRANSFORMASIONAL KEPALA DESA DALAM PENYELENGGARAAN PEMERINTAHAN DI DESA BABAKAN KECAMATAN PANGANDARAN KABUPATEN PANGANDARAN - Misbahudin Misbahudin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The results of observations indicate that the transformational leadership of the Village Head in the implementation of governance has not been fully optimal. This is evident from the lack of coordination with village officials, indecisiveness in decision-making, one-way communication, and the Village Head's limited role in building good relationships with both the community and village apparatus. These conditions have resulted in suboptimal implementation of village development programs and low community participation in governance processes. The method used in this research is qualitative, which involves describing events based on data and facts from the field for analysis and conclusion. The research findings indicate that the transformational leadership of the Head of Babakan Village has not yet reached its optimal level due to the uneven implementation of transformational values, limited human resources, and suboptimal utilization of technology. Although the Village Head has demonstrated visionary and inspirational leadership, the realization of programs and participation of village officials and the community have not yet proceeded in a harmonious manner. Referring to Kharis’s theory (2015), transformational leadership consists of four main aspects: charisma, inspirational motivation, intellectual stimulation, and individualized consideration. The Village Head needs to build subordinates’ self-confidence, provide motivation through a strong vision, encourage innovation, and offer guidance and feedback tailored to individual needs. Through these efforts, a more harmonious, adaptive, and sustainable village governance is expected to be achieved.